2010
DOI: 10.1016/j.jmaa.2009.12.036
|View full text |Cite
|
Sign up to set email alerts
|

A few remarks on divergent sequences: Rates of divergence II

Abstract: We continue (and, in a sense, close) our investigation begun in the paper [10] concerning quotient speed of divergence of sequences of positive real numbers and its relations with selection principles and games. By the way, we show a theorem of the generalized Galambos-Bojanić-Seneta type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(33 reference statements)
0
10
0
2
Order By: Relevance
“…In this paper we begin with a quite different investigation of double sequences related to selection principles and games corresponded to them : for a given sequence X n : n ∈ N of double sequences that belong to one class A we select from each X n a subset Y n by a prescribed procedure so that Y n 's may be arranged to a new double sequence Y which belongs to another class B not necessarily distinct from A of double sequences. For selection principles theory see 14, 15 , and for selection properties of some classes of simple sequences see [16][17][18][19] . Moreover, our investigation suggests also introduction of new selection principles: instead of a sequence of double sequences from a class A we start with a double sequence of double sequences from A see Definitions 2.1 and 2.7 .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we begin with a quite different investigation of double sequences related to selection principles and games corresponded to them : for a given sequence X n : n ∈ N of double sequences that belong to one class A we select from each X n a subset Y n by a prescribed procedure so that Y n 's may be arranged to a new double sequence Y which belongs to another class B not necessarily distinct from A of double sequences. For selection principles theory see 14, 15 , and for selection properties of some classes of simple sequences see [16][17][18][19] . Moreover, our investigation suggests also introduction of new selection principles: instead of a sequence of double sequences from a class A we start with a double sequence of double sequences from A see Definitions 2.1 and 2.7 .…”
Section: Introductionmentioning
confidence: 99%
“…In a number of papers by the authors that appeared recently in the literature it was demonstrated that some classes A and B of sequences of positive real numbers have certain nice selection properties ( [3][4][5][6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…The class P I * is a subclass of the class P I (see e.g. [5]) More information about these classes can be found in [7] and [12].…”
Section: Introductionmentioning
confidence: 99%